2022
DOI: 10.3389/fpls.2022.966929
|View full text |Cite
|
Sign up to set email alerts
|

Plantago lagopus extract as a green fungicide induces systemic resistance against Rhizoctonia root rot disease in tomato plants

Abstract: Extensive use of chemical control agents and fungicides typically leads to numerous risks to human health and the environment. Using plant extracts as natural substances represents a dual key for the environment and sustainable food production, as it reduces the input of synthetic pesticides into the environment and/or controls plant pathogens. For the first time, a Plantago lagopus ethanolic extract has been characterized and evaluated for its protective and curative effects against Rhizoctonia solani in toma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 83 publications
1
13
0
Order By: Relevance
“…PR1 is a crucial regulator of systemic acquired resistance (SAR) and may serve as a marker for early plant defense responses, and its importance in plant immunity has been recognized for over two decades. , The accumulation of PR1 , a SA marker gene, is linked to the activation of SA in response to pathogens . Our results are consistent with previous findings of many studies, indicating that increased PR1 expression enhances resistance against pathogen infections. Several reports have confirmed that PR2 proteins are engaged in various physiological plant defense processes primarily induced by SAR inducers like SA. Increased PR2 activity in plant cell wall has been shown to enhance the accumulation of oligosaccharides produced, which elicits plant defense.…”
Section: Discussionsupporting
confidence: 90%
“…PR1 is a crucial regulator of systemic acquired resistance (SAR) and may serve as a marker for early plant defense responses, and its importance in plant immunity has been recognized for over two decades. , The accumulation of PR1 , a SA marker gene, is linked to the activation of SA in response to pathogens . Our results are consistent with previous findings of many studies, indicating that increased PR1 expression enhances resistance against pathogen infections. Several reports have confirmed that PR2 proteins are engaged in various physiological plant defense processes primarily induced by SAR inducers like SA. Increased PR2 activity in plant cell wall has been shown to enhance the accumulation of oligosaccharides produced, which elicits plant defense.…”
Section: Discussionsupporting
confidence: 90%
“…Meanwhile, Tralamazza et al [15] have reported that this species complex is associated with panicle infection in wild rice in Brazil. Numerous research studies have explored the effectiveness of different extracts against R. solani, revealing encouraging outcomes regarding their antifungal properties [16][17][18]. Antifungal properties towards the fungi Aspergillus flavus, Candida spp., and A. niger were detected using water, alcohol, ether, and chloroform-derived extracts of S. macrophylla leaves [19].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, the richness of P . lagopus ethanolic extracts in rutin, naringenin, quercetin, p-hydroxybenzoic acid, ellagic acid, vanillic acid, catechol, cinnamic acid, ferulic acid, benzoic acid and chlorogenic acid was provided [ 14 ]. Grubešić et al in a comparative study among different species in Croatia, evidenced that methanolic extracts of P .…”
Section: Discussionmentioning
confidence: 99%
“…While, iridoid and phenyethanoid glycosides are metabolites isolated from P . lagopus L. with nutritional and allelopathic properties [ 10 14 ]. In addition, it was reported that verbascoside and calceorioside A were present in leaf extracts of P .…”
Section: Introductionmentioning
confidence: 99%